2012
DOI: 10.1371/journal.pone.0032347
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Close to the Edge: An Immunosuppressive Infiltrate in the Chorionic Plate of Placentas from Uncomplicated Egg Cell Donation

Abstract: In pregnancies achieved after egg donation (ED) tolerance towards a completely allogeneic fetus is mediated by several complex immunoregulatory mechanisms, of which numerous aspects are still unknown. A distinct lesion not described previously in the literature, was repeatedly found in the chorionic plate in a substantial portion of placentas from ED pregnancies, but never in placentas from normal term pregnancies. The aim of this study was to assess its origin and its cellular composition. The relation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 27 publications
0
23
1
1
Order By: Relevance
“…Intriguingly, Schonkeren et al showed a significantly higher incidence of the fetal HLA-C2 genotype in pregnancies with a distinct lesion in the chorionic plate of uncomplicated OD pregnancies. This lesion was not observed in placentas from preeclamptic OD pregnancies and an immunological protective mechanism against the allogeneic fetus was suggested (Schonkeren et al, 2012). Indeed, in the group that showed this lesion the fetal C2 was more often combined with the protective maternal haplotype KIR B (Schonkeren et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Intriguingly, Schonkeren et al showed a significantly higher incidence of the fetal HLA-C2 genotype in pregnancies with a distinct lesion in the chorionic plate of uncomplicated OD pregnancies. This lesion was not observed in placentas from preeclamptic OD pregnancies and an immunological protective mechanism against the allogeneic fetus was suggested (Schonkeren et al, 2012). Indeed, in the group that showed this lesion the fetal C2 was more often combined with the protective maternal haplotype KIR B (Schonkeren et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…This lesion was not observed in placentas from preeclamptic OD pregnancies and an immunological protective mechanism against the allogeneic fetus was suggested (Schonkeren et al, 2012). Indeed, in the group that showed this lesion the fetal C2 was more often combined with the protective maternal haplotype KIR B (Schonkeren et al, 2012). However, the number of patients was small and the frequency of KIR A/fetal C2 combination should be tested in preeclamptic OD pregnancies, regardless of the chorionic plate lesion, and in spontaneously aborted OD pregnancies.…”
Section: Discussionmentioning
confidence: 92%
“…3) [63]. Interestingly, when inflammatory lesions are found in the chorionic plate in OD pregnancy, the incidence of preeclampsia is very low (0 %), while preeclampsia shows a very high incidence (45.5 %) when inflammation of the chorionic plate is not detected [63].…”
Section: Placental Pathology In Od Pregnancymentioning
confidence: 99%
“…In ovodonated mothers, unique and typical immune-adaptive changes are found in successful pregnancies, but not in those developing preeclampsia [ 44 ].…”
Section: Dyslipidaemia and Late Decidual Changesmentioning
confidence: 99%